Studi Potensi Interaksi Obat Pasien Covid-19 di Rumah Sakit Umum Daerah Kota Mataram: Study on The Potential Drug Interactions in COVID-19 Patient at the Mataram City General Hospital - Dwi Monika Ningrum; Putri Ramdaniah; Denih Agus Setia Permana; Deny Hariyadi (Indonesian Journal of Pharmacy and Natural Product, 2023)
Covid-19 or Coronavirus disease 2019 is an acute respiratory disease caused by the Severe Acute Respiratory Syndrom Coronavirus (SARS CoV-2), which entered Indonesia in early 2020. Data on Covid-19 in West Nusa Tenggara Province (NTB) in November reported 4,550 cases. Covid-19 can cause disorders in the respiratory system, acute pneumonia to death, so researchers conducted this study which aims to see how potential drug interactions exist in patients who get Covid-19 therapy while being treated at the Mataram City Hospital for the January-December 2021 period. This research is a descriptive study conducted to get an idea of whether there are potential drug interactions that occur by conducting research objectively. Data obtained from primary data, namely medical records of patients diagnosed with Covid-19 and treated in isolation rooms. Obtained as many as 95 medical record data of Covid-19 patients in the period January - December 2021. This research is a descriptive study conducted to get an idea of whether there are potential drug interactions that occur by conducting research objectively. Data obtained from primary data, namely medical records of patients diagnosed with Covid-19 and treated in isolation rooms. As many as 95 medical record data for Covid-19 patients were obtained in the period January – December 2021. Of the 95 patients obtained, it was found that the category of drug interactions with drugs based on severity was 5.26%, moderate interactions were 42.10%, and major interactions were 3.15%.  The conclusion of this study is that the most common potential drug interactions were found with moderate severity with a percentage of 42.10% of 95 patients. ABSTRAK Covid-19 atau Coronavirus disease 2019 merupakan suatu penyakit pernapasan akut yang disebabkan oleh Severe Acute Respiratory Syndrom Coronavirus (SARS CoV-2), yang masuk ke Indonesia di awal tahun 2020. Data Covid-19 di Provinsi Nusa Tenggara Barat (NTB) pada bulan November dilaporkan sebanyak 4.550 kasus. Covid-19 dapat menyebakan gangguan pada sistem pernapasan, pneumonia akut hingga kematian, sehingga peneliti melakukan penelitian ini yang  bertujuan untuk melihat bagaimana potensi adanya interaksi obat pada pasien yang mendapatkan terapi Covid-19 selama di rawat di RSUD Kota Mataram periode Januari-Desember 2021. Penelitian ini merupakan penelitian deskriptif yang dilakukan untuk mendapatkan gambaran apakah ada potensi interaksi obat yang terjadi dengan melakukan penelitian secara objektif. Data diperoleh dari data primer yaitu rekam medis pasien yang terdiagnosa Covid-19 dan dirawat di ruang isolasi. Diperoleh sebanyak 95 data rekam medis pasien Covid-19 pada periode Januari – Desember 2021. Dari 95 pasien yang diperoleh, ditemukan diperoleh kategori interaksi obat dengan obat berdasarkan keparahan yaitu interaksi minor sebanyak 5,26% , interaksi moderate 42,10% , dan interaksi mayor sebanyak 3,15%.  Kesimpulan penelitian ini adalah potensi interaksi obat yang paling banyak ditemukan yaitu dengan tingkat keparahan moderate dengan persentase sebesar yaitu 42,10% dari 95 pasien.